Análise de performance e gestão de fundos de investimento multimercados no Brasil - Nogueira, Thiago Alves (2012)
This work analyzes the performance graph and quantitative metrics under different gain, volatility, skewness, kurtosis and dynamic performance of portfolios composed of 85 investment funds Hedge in Brazil, vis-à-vis the major market benchmarks and traditional options investments. In this context, this empirical study is aligned with Matos e Artur (2011) strategies to address dynamic composition during the period 2005 to 2010, annual basis, containing the 10 winners and 10 funds Loosers. In scenarios characterized by economic boom or recovery of financial markets, the adoption of active strategies in funds winners in performance, equal stakes, provides increases in average earnings, risk reduction associated with diversification and thus increase performance in relation the benchmarks. This evidence is robust to the use of different performance metrics for the selection of funds. The strategy proposed activity is such that the investor bets each year in the 10 funds with better performance (winners) in Calmar, in Sharpe, Treynor and Sortino in. Analyses were also the same strategy, but buying the 10 funds with the worst performance (Loosers). According to the results, the annual ranking of Hedge Funds is very robust to changes in the performance metric used. The portfolios consist of the winners have funds throughout the period accumulated higher real earnings, the real gain around 25% higher than that obtained by the Savings and about 16% of funds portfolios Loosers. During the pre-crisis real earnings ranged between winners and Loosers during the period between the different portfolios, while in times of crisis real earnings of the Fund winners were around 35% higher than those obtained by the Funds Loosers. Noteworthy is the high performance, in absolute terms, with funds of winners portfolios compared to the savings, as well as the superiority in relation to portfolios with funds Loosers, a robust evidence consequence of technical expertise winners of funds and high risk exposure funds Loosers.